If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1n = -6 + -3n Solving 6 + -1n = -6 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 6 + -1n + 3n = -6 + -3n + 3n Combine like terms: -1n + 3n = 2n 6 + 2n = -6 + -3n + 3n Combine like terms: -3n + 3n = 0 6 + 2n = -6 + 0 6 + 2n = -6 Add '-6' to each side of the equation. 6 + -6 + 2n = -6 + -6 Combine like terms: 6 + -6 = 0 0 + 2n = -6 + -6 2n = -6 + -6 Combine like terms: -6 + -6 = -12 2n = -12 Divide each side by '2'. n = -6 Simplifying n = -6
| 3x+6-4x+12=12 | | 110=39.41+.25x | | 12=4x+5 | | (4x-3)(8x+6)= | | 5x+19=2x+1 | | 0.6-0.6(7-3)=1.5(2.8-1)-3 | | 5x+1+6=21 | | 0.6-0.6(4-3)=1.5(1.6-1)-3 | | 2.5(x+2)=4.5x-5 | | u-60=u | | 2(9y+2)=15y+28 | | -2n-12=4n | | 4x^2-23x+38=4x+3 | | 2.5x=4 | | 5(m-3)+2(3m+1)=15-8 | | -5m(m-3)+2(3m+1)=15-8 | | 7(x-1)-3.5x=2.5x+5 | | 4m^2-5m-21=0 | | 8y-3=8y | | n-(3)-12=-24 | | 13x+4x= | | x+5=2(x+3) | | 3x+5=195 | | n-(-15)=-29 | | 3(4x+3y)+4(3x+y)= | | -4x+7y=16 | | (4x-4)(3x+4)=0 | | 3(x+4)+2x=5(x+2) | | n-8=-21 | | -5n(5n-6)=0 | | 3r^2+3r-6=0 | | -2y=-4y+24 |